G115(P) Retinopathy of prematurity – keeping an eye on the screening programme. (7th April 2014) - Barker, RV; Farooq, T; Venugopalan, V; Butler, L
Abstract : Background: Retinopathy of prematurity (ROP) is a cause of treatable blindness in premature babies. Guidelines in the UK recommend babies born at less than 32 weeks gestation or weighing less than 1501 grams are screened to enable the timely provision of treatment of sight threatening ROP. Clinical audit was done to explore the effectiveness of the ROP screening service provided by an ophthalmologist at a teaching hospital. Effectiveness was determined by adherence to guidelines regarding (a) referral to screening programme; (b) appropriate repeat screening and discharge and (c) appropriate and timely treatment. The standard of an effective service was set at 100% adherence to guidelines. Methods: Details of all babies who were admitted to the neonatal unit between 01/04/12 and 31/03/13 were collected. The details of the babies admitted were compared to the babies who were recorded by the ophthalmologist to have received screening for ROP and records on the trust intranet. Results: According to the guidelines, 151/991 (15.24%) babies were eligible for ROP screening during this time period. 135/151 (89.4%) babies who should receive ROP screening did receive it. Of those that did not receive screening, 16/16 (100%) had a sufficient reason for not receiving screening (too young to screen as inpatient, died or transferred prior to entry). 112/135 (82.96%) received appropriate repeat screening and discharge. Of the 23 who did not, 11 were transferred, 1 died, 1 refused, 5 did not attend and 4 had delayed screening due to transfer in and 1/135 (0.74%) was lost to follow up. 1/151 (0.66%) baby required laser treatment for ROP and this was done at the right time. Conclusion: Evaluation demonstrated that the neonatal unit and ROP screening service worked together to adhere to guidelines 100% of the time when factors were within the hospital's control. Although it is difficult to alter factors outside its control, the hospital should work to reduce the number of 'did not attend' babies, by improving knowledge of ROP through patient information leaflets and staff-parent discussion.